Avaliação da importância dos sistemas de gestão da qualidade nas universidades federais - Andrade, Dalliane Vanessa Pires (2013)
This thesis aims at analyzing from the perspective of the manager the importance of the use of quality management tools and concepts in Federal Universities. It was motivated by the following research problem: do Federal University managers consider it to be relevant the quality management in their institution? Therefore, we sought to gather evidence for a satisfactory approach that addresses the complexity of the topic researched: quality, higher education and quality management systems. We chose to adopt an applied study, the exploratory-descriptive research as to the objective and the quantitative and qualitative research as to the approach to the problem. The object of study is composed by the Planning Provosts of Federal Universities listed in the University Ranking Sheet - (RUF) in 2013. We chose to restrict the sample listing only the provosts of the 20 best-placed universities in the ranking of the Federal Universities. The research instrument was composed of 26 questions, of which 6 questions were designed to identify the profile of the manager, 16 questions of perception (manifested variables) on the importance of quality management in the University, where the managers assigned values (answers) to the affirmatives (that address the main topic of this thesis) based on a Likert scale of 5 points, and 4 open and optional questions, in order to identify general management practices used. It was used for statistical analysis (data analysis) descriptive and factorial statistics. The responses collected through the questionnaire portray the managers´ perception regarding the importance of quality management in their institutions. Sixteen variables were addressed, the results of factor analysis of importance were "Important" and "Very Important", where the variable (V2) was "Important" and all others "Very important." With this information, it is possible to prioritize some areas that deserve immediate action. As it was observed that some variables are "Very important" for the vast majority of managers, others did not show the same result as example (V2, V10, V11). It is concluded that the manager´s perception of quality management in his or her institution is relevant, but the same importance is not given to quality programs implemented in other segments of the economy, and that, despite the advancements offered by SINAES, the model does not evaluate the institution in a global way. Thus, with the results, it is expected to contribute to the advancement of the subject, trying to arouse interest from the managers of Federal Universities in the subject, emphasizing the importance of quality management systems as a necessary tool to raise the institutional quality